Analysis of the Translation of Anger Expressions in the Novel 'Pride and Prejudice' by Jane Austen - Sulistini Dwi Putranti; Aisha Rizki Mahirani (International Journal of Education and Humanities, 2023)
This paper is aimed at providing a comprehensive analysis of the types and techniques used in translating expressions of anger found in Jane Austen's novel entitled Pride and Prejudice by using Molina and Albir’s (2012) translation techniques and Madow’s Theory of Anger. The study uses a qualitative method to describe and analyze all the data. There are 33 data points on anger expressions found, and each finding reveals that direct and indirect anger expressions are the most common types of anger found in both novels, which are then followed by thinly veiled expressions. Among the 18 translation techniques, transposition emerges as the most frequently applied, indicating the significance of restructuring the source text to suit the target language while still preserving the original meaning. Amplification, adaptation, variation, and literal translation are the next frequently used techniques, emphasizing the translator’s efforts to deliver the emotional situations of anger expressions. Additionally, the study highlights the importance of linguistic compression and amplification in maintaining the emotional impact of anger expressions across languages. In general, this research focuses on the complexities and techniques used in translating expressions of anger, making significant contributions and offering valuable perspectives for future translation studies